Coupled Arsenotrophy in a Hot Spring Photosynthetic Biofilm at Mono Lake, California - Hoeft, Shelley E. (American Society for Microbiology (ASM), 2010)
Red-pigmented biofilms grow on rock and cobble surfaces present in anoxic hot springs located on Paoha Island in Mono Lake. The bacterial community was dominated (∼ 85% of 16S rRNA gene clones) by sequences from the photosynthetic Ectothiorhodospira genus. Scraped biofilm materials incubated under anoxic conditions rapidly oxidized As(III) to As(V) in the light via anoxygenic photosynthesis but could also readily reduce As(V) to As(III) in the dark at comparable rates. Back-labeling experiments with (73)As(V) demonstrated that reduction to (73)As(III) also occurred in the light, thereby illustrating the cooccurrence of these two anaerobic processes as an example of closely coupled arsenotrophy. Oxic biofilms also oxidized As(III) to As(V). Biofilms incubated with [(14)C]acetate oxidized the radiolabel to (14)CO(2) in the light but not the dark, indicating a capacity for photoheterotrophy but not chemoheterotrophy. Anoxic, dark-incubated samples demonstrated As(V) reduction linked to additions of hydrogen or sulfide but not acetate. Chemoautotrophy linked to As(V) as measured by dark fixation of [(14)C]bicarbonate into cell material was stimulated by either H(2) or HS(−). Functional genes for the arsenate respiratory reductase (arrA) and arsenic resistance (arsB) were detected in sequenced amplicons of extracted DNA, with about half of the arrA sequences closely related (∼98% translated amino acid identity) to those from the family Ectothiorhodospiraceae. Surprisingly, no authentic PCR products for arsenite oxidase (aoxB) were obtained, despite observing aerobic arsenite oxidation activity. Collectively, these results demonstrate close linkages of these arsenic redox processes occurring within these biofilms.